Pengembangan Video Tutorial Berbasis YouTube Tari Canting Kahuripan untuk Meningkatkan Kemampuan Menari Siswa SMP - Joko Saputra; Anik Juwariyah; Setyo Yanuartuti; Indar Sabri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to describe the process of developing video tutorial learning materials for the Canting Kahuripan Dance. Batik Gedog Tuban is used to design the content and form of the Canting Kahuripan Dance as learning materials packaged through learning videos. The method used in this study is the R&D (Research and Development) method with the 4D development model (Definition, Design, Develop, Distribute) which aims to create or refine new products to solve learning problems. The research subjects were seventh-grade students of SMP Negeri 3 Tuban. Data were collected through interviews, observations, questionnaires, and learning outcome tests. The validation results by material experts and media experts showed that the product was feasible to use with a feasibility percentage of 87.5% and 85%, respectively. Teachers' and students' responses to the video tutorial were very positive with a practicality percentage of 88% and 86%, respectively. Student learning outcomes increased significantly from an average pretest of 65 to a posttest of 82. The conclusion of the study shows that the YouTube-based Canting Kahuripan dance tutorial video is effective in improving students' dancing skills and is suitable for use as a learning medium. The results of the study show that the developed teaching material products are in accordance with the contents of the Merdeka curriculum for the Arts and Culture subject in the field of dance in points that contain matters related to improving students' abilities in understanding and practicing traditional dance material.